Effect of hybridization on properties of hemp-carbon fibre-reinforced hybrid polymer composites using experimental and finite element analysis - Ramesh, M.; Deepa, C.; Arpitha, G.R.; Gopinath, Venkatraman (Emerald, 2019)
Purpose: In the recent years, the industries show interest in natural and synthetic fibre-reinforced hybrid composites due to weight reduction and environmental reasons. The purpose of this experimental study is to investigate the properties of the hybrid composites fabricated by using carbon, untreated and alkaline-treated hemp fibres. Design/methodology/approach: The composites were tested for strengths under tensile, flexural, impact and shear loadings, and the water absorption characteristics were also observed. The finite element analysis (FEA) was carried out to analyse the elastic behaviour of the composites and predict the strength by using ANSYS 15.0. Findings: From the experimental results, it is observed that the hybrid composites can withstand the maximum tensile strength of 61.4 MPa, flexural strength of 122.4 MPa, impact strength of 4.2 J/mm 2 and shear strength of 25.5 MPa. From the FEA results, it is found that the maximum stress during tensile, flexural and impact loading is 47.5, 2.1 and 1.03 MPa, respectively. Originality/value: The results of the untreated and alkaline-treated hemp-carbon fibre composites were compared and found that the alkaline-treated composites perform better in terms of mechanical properties. Then, the ANSYS-predicted values were compared with the experimental results, and it was found that there is a high correlation occurs between the untreated and alkali-treated hemp-carbon fibre composites. The internal structure of the broken surfaces of the composite samples was analysed using a scanning electron microscopy (SEM) analysis. © 2019, Emerald Publishing Limited.